2021
DOI: 10.3855/jidc.14826
|View full text |Cite
|
Sign up to set email alerts
|

Does C reactive protein/Albumin ratio have prognostic value in patients with COVID-19

Abstract: Introduction: There is paucity of data regarding C reactive protein/Albumin (CRP/Alb) ratio in patients with SARS-CoV-2 infection. We aimed to evaluate the significance of CRP/Alb ratio in COVID-19 patients. Methodology: Patients hospitalized between March – April 2020 with COVID-19, who had CRP and Albumin levels documented within 24 hours from admission were retrospectively analyzed. Unpaired Student’s t-test was used for continuous and Pearson Chi-square (χ²) test for categorical variables. Univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Comorbidities and aggravating factors which are more common in patients over the age of 65, may be contributing to the high mortality rate in patients with high CAR. It has been reported in the literature that high CRP and low albumin levels are associated with the severity of the disease in Covid-19 and these findings are also physiological in advanced age 8,10,14,18 . This led us to believe that the CAR in advanced age may be more important in determining the severity of Covid-19.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Comorbidities and aggravating factors which are more common in patients over the age of 65, may be contributing to the high mortality rate in patients with high CAR. It has been reported in the literature that high CRP and low albumin levels are associated with the severity of the disease in Covid-19 and these findings are also physiological in advanced age 8,10,14,18 . This led us to believe that the CAR in advanced age may be more important in determining the severity of Covid-19.…”
Section: Discussionmentioning
confidence: 82%
“…CRP to albumin ratio (CAR), which is the ratio of these two laboratory parameters to one another, and is used to assess the patient's inflammation and nutritional status and it is known to be a prognostic factor in cases of malignancy and severe disease 7 . In recent studies, it has been emphasized that CAR may be a promising prognostic biomarker for risk stratification and clinical management of patients with severe Covid-19 and can be an early predictor of disease progression 10 .…”
Section: Introductionmentioning
confidence: 99%
“…After exclusions, 23 studies with a total of 7774 participants remained and were ultimately included in the analysis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 The process of study selection is summarised in Supplementary Figure 1 using the PRISMAflowchart. Sixteen studies reported the association of CAR with COVID‐19 outcomes, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 four studies included FAR, 28 , 29 , 30 , 31 and three studies included both CAR and FAR.…”
Section: Resultsmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 The process of study selection is summarised in Supplementary Figure 1 using the PRISMAflowchart. Sixteen studies reported the association of CAR with COVID‐19 outcomes, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 four studies included FAR, 28 , 29 , 30 , 31 and three studies included both CAR and FAR. 32 , 33 , 34 Table 1 outlines the study characteristics of the included articles, while Table 2 summarises the optimal cut‐off, the area under the curve (AUC), sensitivity, and specificity of CAR and FAR for predicting COVID‐19 mortality and severity.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] In recent studies, it has been emphasized that CAR may be a promising prognostic biomarker for risk stratification and clinical management of patients with severe COVID-19 and can be an early predictor of disease progression. [26,27] In this study, we assumed that CAR alone can be a stronger prognostic parameter than CRP and albumin in predicting clinical severity and mortality in hospitalized patients with a diagnosis of COVID 19. We determined that the level of serum CAR, both in patients who are hospitalized in the intensive care unit and who died after treatment due to COVID-19 infection, was significantly higher than patients who were followed-up in service and who were alive.…”
Section: Discussionmentioning
confidence: 99%